2013
DOI: 10.3389/fnagi.2013.00058
|View full text |Cite
|
Sign up to set email alerts
|

Integrative EEG biomarkers predict progression to Alzheimer's disease at the MCI stage

Abstract: Alzheimer's disease (AD) is a devastating disorder of increasing prevalence in modern society. Mild cognitive impairment (MCI) is considered a transitional stage between normal aging and AD; however, not all subjects with MCI progress to AD. Prediction of conversion to AD at an early stage would enable an earlier, and potentially more effective, treatment of AD. Electroencephalography (EEG) biomarkers would provide a non-invasive and relatively cheap screening tool to predict conversion to AD; however, traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
124
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(136 citation statements)
references
References 101 publications
11
124
0
1
Order By: Relevance
“…In addition to imaging biomarkers, one study found that the six electroencephalography biomarkers on electroencephalography could predicte MCI to AD conversion in the Alzheimer’s Center in Netherlands (43). Two studies used clinical tests to predict MCI to AD conversion.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to imaging biomarkers, one study found that the six electroencephalography biomarkers on electroencephalography could predicte MCI to AD conversion in the Alzheimer’s Center in Netherlands (43). Two studies used clinical tests to predict MCI to AD conversion.…”
Section: Resultsmentioning
confidence: 99%
“…Subtle but consistent deviations in the electromagnetic neuronal dynamics have been shown to precede explicit cognitive manifestations in AD [291] which could enable a future role of EEG/MEG biomarkers not only as a clinical diagnosis and treatment option, but also as a new mode for AD stage discovery. Dramatic progresses in dense-array active-EEG and MEG sensor technology, as well as in advanced signal processing techniques [292] have generated a recent surge of interest to use these promising capabilities in the context of improved clinical AD diagnosis. The added value of the EEG/MEG markers as an inexpensive, fast, and time-resolved tool is set to be explored rigorously both as a standalone approach and as a complementary measure together with other biomarker modalities.…”
Section: Neuroelectrical and Neuromagnetic Markersmentioning
confidence: 99%
“…A next generation of more sophisticated resting-state signal analysis approaches [292] is set to improve upon and to replace band-power markers in the next decade by capturing better the complex characteristics and dynamics of progressive neurodegeneration and aging. Promising methods involve brain connectivity [296], global synchronization, synchronization likelihood [291], detrended fluctuation analysis, approximate entropy, mutual information, source localization, and a host of further non-linear signal features.…”
Section: Resting-state Neuroelectrical/neuromagnetic Markersmentioning
confidence: 99%
“…Changes in power were analyzed by using the Neurophysiological Biomarker Toolbox 15 and compared with 5-minute EEG recordings of 15 agematched (9-11 years old) healthy subjects with normal development. These data were collected as part of the Dutch Dyslexia Programme (DDP).…”
Section: Figurementioning
confidence: 99%